PERANAN ATASAN BERHAK MENGHUKUM DAN PERWIRA PENYERAH PERKARA DALAM PROSES PENYELESAIAN PERKARA TINDAK PIDANA DESERSI DI PERADILAN MILITER - Erlangga Prasady; Alvi Syahrin; Madiasa Ablisar; Edi Yunara (USU LAW JOURNAL, 2018)
ABSTARCT This research analyzed  about Ankum and Papera are crucial to the work of the military justice process. The propriety of investigators and investigators of military crimes can be disrupted by the superior-subordinate mechanisms. And in practice there is often an interesting attraction between Ankum on the one hand with law enforcement officers on the other. Law enforcement officials have an interest in bringing the suspect to court, while Ankum / Papera tends to avoid because bringing to justice is equally concerned about Ankum's responsibilities as commander. The type of this research is legal / normative research and descriptive analysis. The problem approach used in this research is statute approach and conceptual approach, collecting and collecting data is done by literature study and field study, research It uses qualitative analysis. Based on Law Number 31 of 1997 The role and authority of Ankun as commander of a commander has a central position and fully responsible for his subordinates. Papera in determining a criminal case to seek opinions from Oditur Miilter but its nature in the form of suggestions and opinions then it does not bind the commanders, ultimately the commander is also decisive so that the assessment is subjective when the settlement of a case must be objective.   Keywords: Role, Ankum, Papera, Crime Desertion, Military Court